Wound complication after modified Ravitch for pectus excavatum: A case of conservative treatment enhanced by pectoralis muscle transposition. (2020) - Aramini, Beatrice; Morandi, Uliano; De Santis, Giorgio; Brugioni, Lucio; Stefani, Alessandro; Ruggiero, Ciro; Baccarani, Alessio
Highlights: Vacuum-assisted closure is a well-established technical resource for treating complicated wounds. In cases of suspicion of bone infection, VAC therapy is not enough to prevent bar removal. Multiple surgical debridement sessions are mandatory before wound closure in cases of infection. We present a case of surgical wound dehiscence with hardware exposure. After VAC therapy and surgical debridement, the bilateral pectoralis muscle flap mobilization has been used. Abstract: Introduction: Multiple surgical debridement sessions are mandatory before wound closure in cases of infection after a modified Ravitch procedure for pectus excavatum. Vacuum-assisted closure (VAC) is a well-established technical resource for treating complicated wounds; however, in cases of suspicion of bone infection, this approach is not enough to prevent bar removal. Presentation of the case: We present a case of surgical wound dehiscence with hardware exposure in a patient who had undergone chondrosternoplasty for pectus excavatum. Several sessions of debridement (three) and VAC were applied every time. The final result was achieved without the necessity to remove the hardware; however, to avoid the risk of infection, a bilateral pectoralis muscle flap mobilization was performed as the final step after the surgical wound revisions, although this approach is suggested to be used during the modified Ravitch procedure. This approach allows for a significant reduction in late complications and improves morphological outcomes. Discussion: In summary, the pectoralis muscle flap transposition is very useful not only for aesthetical results but also in combination with multiple surgical revisions for conservative management in case of wound infection during a modified Ravitch procedure. In our case, this technique was adopted after accurate care of the wound and before the final closure, which helps to maintain good vascularization and a very satisfying result. Conclusion: It is important to consider this approach during the modified Ravitch procedure, not only for better aesthetical results but also to prevent infections or wound dehiscence at the level of the bar.